Association between Board Characteristics and Accounting Conservatism: empirical evidence from Malaysia - Ho, Joo Ann (Auckland University of Technology, 2009)
This paper examines the association between board characteristics and accounting conservatism using a sample of 716 Malaysian listed firms for the year 2008. I use five board characteristics, namely the percentage of inside directors, CEO/Chairman separation, board size, board meetings and managerial ownership. Utilising three different measures of conservatism, I find that (i) percentage of inside directors is negatively related to conservatism and (ii) board size is negatively related to conservatism. Results hold after controlling for firm size, sales growth, profitability and leverage. These findings are consistent with previous studies by Beekes et al. (2004), Ahmed and Duellman (2007) and García Lara et al. (2007). Overall, my evidence shows that firms with strong boards use conservative reporting as a governance tool, even in a unique institutional setting like Malaysia.
Keywords: Accounting conservatism; Malaysia; Corporate governance; Board characteristics